Celebrating the East: The Contestation of Whiteness and Colored in John M. Chu’s Crazy Rich Asians - Rif'ah Inayati; Ida Rochani Adi; Muh. Arif Rokhman (Universitas Gadjah Mada, 2022)
Crazy Rich Asians is regarded as one of the movies that successfully represented Asians, regardless of all the controversy. One of the topics clearly presented in the movie is the contestation between the west and east. The dichotomy is resulted from the social construction of the western culture to maintain its superiority over the east culture. Since the movie seems to celebrate the east by portraying the Asian-Asians differently from the old stereotypes or old images of the eastern culture, but at the same time, this research finds that this movie overtly portrays the west as loveable or likable culture. The movie depicts the contrast between east and west through the story. This article is intended to analyze the contestation between east and west which is depicted in the movie. The movie is examined in how it depicts America as the west and Asia as part of the east. Therefore, deconstruction is used as the reading method to see what is behind it, the things that are not seen, related to how the Asians are portrayed in the movie. The finding of this research shows that there are double roles in the movie. The power of whiteness in the American movie industry somehow still brings impacts toward the contestation of whiteness and color.